Application of Inverse Perspective Mapping for Advanced Driver Assistance Systems in Automotive Embedded Systems - Vighnesh N.T; Rachana Anil; Rohith Kumar D; Sanjana Sharvana; Rajeshwari Hegde; B S Nagabhushana (International Journal of Reconfigurable and Embedded Systems (IJRES), 2017)
In the recent times vehicle manufactures and automotive suppliers are progressing towards building vision based subsystems for provisioning driver assistance while targeting the automotive safety critical needs. While the acquired images constitute the fundamental input for any vision based system, transforms on images become essential to derive and gain insight into certain specific features. These derived features are used and reused at multiple places for varied automotive applications. This situation warrants a scalable and flexible image processing platform for a class of automotive applications. An attempt is made in this Research work to propose architecture that, specially, includes a layer of image transformations and to implement a prototype image processing platform. Inverse Perspective Mapping (IPM), a widely used class of transforms is emphasized in the present architecture alongside other nominal transforms. Lane departure warning system is implemented on this platform for the purpose of illustration and to analyze the effectiveness of the proposed architecture